2018
DOI: 10.1038/s41598-017-18410-x
|View full text |Cite|
|
Sign up to set email alerts
|

Dial-in Topological Metamaterials Based on Bistable Stewart Platform

Abstract: Recently, there have been significant efforts to guide mechanical energy in structures by relying on a novel topological framework popularized by the discovery of topological insulators. Here, we propose a topological metamaterial system based on the design of the Stewart Platform, which can not only guide mechanical waves robustly in a desired path, but also can be tuned in situ to change this wave path at will. Without resorting to any active materials, the current system harnesses bistablilty in its unit ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 31 publications
2
35
0
Order By: Relevance
“…Despite these drawbacks, the trends shown in figure C1 are evident enough to demonstrate the efficient wave transmission along the bent paths. We also note in passing that the authors' previous studies have numerically shown the clear distinctions between topological and trivial waveguiding using a uniform platform of dial-in topological metamaterials [17].…”
Section: Appendix C Wave Transmission Efficiency Quantificationmentioning
confidence: 71%
See 1 more Smart Citation
“…Despite these drawbacks, the trends shown in figure C1 are evident enough to demonstrate the efficient wave transmission along the bent paths. We also note in passing that the authors' previous studies have numerically shown the clear distinctions between topological and trivial waveguiding using a uniform platform of dial-in topological metamaterials [17].…”
Section: Appendix C Wave Transmission Efficiency Quantificationmentioning
confidence: 71%
“…This tool of topology has paved a way for researchers to control the flow of energy in other areas, such as photonics [3] and acoustics [4][5][6][7]. It has also given an impetus to a new way of designing elastic systems [8][9][10][11][12][13][14][15][16][17][18][19]. These topological structures-mostly in the setting of discrete lattices or perforated structures-aim at manipulating elastic vibrations and offer a tremendous degree of flexibility in controlling their dynamic responses.…”
Section: Introductionmentioning
confidence: 99%
“…QVHE is analogous to QSHE: the valley index in QVHE plays a similar role of spin in QSHE, in mimicking the QHE-like states without breaking the TR symmetry [7]. Acoustic/elastic analogies of QSHE and QVHE have been a hot research topic and a comprehensive review of theoretical and experimental works on this field can be found in [24][25][26][27][28][29][30][31][32].…”
Section: List Of Symbolsmentioning
confidence: 99%
“…Some novel directions came in recent years from the field of topological acoustics. Owing to the many similarities (both at mathematical and physical level) between acoustics and the wave nature of electrons, researchers have recently leveraged the groundbreaking discoveries of topological phases of matter [17,18] and created their acoustic analogues [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Among the most significant properties of topological materials, there is certainly the ability to induce chiral and backscattering-immune edge states supported at the boundaries of topologically different materials.…”
Section: Introductionmentioning
confidence: 99%
“…Only in very recent years, researchers have explored the possibility to design both acoustic and elastic topological waveguides by exploiting the acoustic analogue of the quantum valley Hall effect (QVHE; aoustic valley Hall effect, AVHE) [28][29][30][31][32][33][34][35][36][37][38]. The underlying mechanism of the QVHE/AVHE requires only space-inversion symmetry (SIS) breaking in a lattice that possesses Dirac dispersion at the high symmetry points.…”
Section: Introductionmentioning
confidence: 99%